Mycoplasma leachii causes bovine mastitis: Evidence from clinical symptoms, histopathology and immunohistochemistry - Ji-tao CHANG; De-bin YU; Jian-bin LIANG; Jia CHEN; Jian-fa WANG; Fang WANG; Zhi-gang JIANG; Xi-jun HE; Rui WU; Li YU (Journal of Integrative Agriculture, 2019)
Twelve quarters of six lactating cows were inoculated with Mycoplasma leachii strain GN407 through intramammary ductal infusion; another 12 quarters were inoculated with heat-inactivated M. leachii culture medium as negative controls. Multidisciplinary procedures, including clinical assessment, etiology assessment, pathology and immunohistochemistry (IHC), were used to elucidate the pathogenicity of M. leachii in bovine mastitis. From post-inoculation days (PIDs) 3 to 9, 12 inoculated quarters developed mild to severe clinical mastitis and mammary tissue histopathological changes, including inflammatory cell infiltration and architectural destruction of mammary gland ducts. The M. leachii antigen was also detected by IHC in the mammary gland epithelial cells of the inoculated quarters as a weak signal on PID 6 and as a strong signal on PID 9. The control quarters also developed mild mastitis and histopathological changes on PID 9, and M. leachii was also detected by IHC. Throughout the experimental period, the quarters of the negative control cow were clinically and pathologically normal, and the M. leachii antigen was not detected. In conclusion, direct histological and immunohistochemical evidence confirmed that M. leachii causes clinical bovine mastitis through histopathological lesions induced by invasion of the pathogen into mammary gland cells and through inflammatory cell infiltration.